Assessment Of Ambient-Noise Exposure Among Female Nurses In Surgical Cardiac Intensive Care Unit - Alduais SA; Salama KF (Journal of Multidisciplinary Healthcare, 2019)
Safa A Alduais,1 Khaled F Salama2 1Saud Albabtain Cardiac Center, Dammam, Saudi Arabia; 2Department of Environmental Health, College of Public Health, Imam Abdulrahman Bin Faisal University, Dammam, Saudi ArabiaCorrespondence: Khaled F SalamaDepartment of Environmental Health, College of Public Health, Imam Abdul Rahman Bin Faisal University, PO Box 1982, Dammam 31441, Saudi ArabiaEmail ksalama@iau.edu.saPurpose: To measure noise levels in the Saud Albabtain Cardiac Center cardiac surgical intensive-care unit (CSICU) at different locations to find out the prevalence of noise-induced hearing loss among female nurses.Methods: Ambient CSICU noise was measured using a sound-level meter and personal noise dosimeter during morning and night shifts (12 hours each) for 30 days. An audiometry test and questionnaire were used to test nursing responses to noise levels.Results: Mean 12-hour average noise levels at the station during night shift were 60.3±7.1 dB(A) and inside rooms 62.48±8.02 dB(A). However, during morning shift 64.1±8.4 dB(A) in the rooms was recorded, while 68.8±8.2 dB(A) was recorded at the station, with a significant difference between the shifts (p<0.0001). ICU monitors recorded the highest noise-source levels of 82.7±5.3 dB(A). The lowest significant source was the suction machines, with an average of 67.1±12.5 dB(A). A significant correlation between decibel loss and nurse experience was observed.Conclusion: Noise levels in the CSICU at Saud Albabtain Cardiac Center were higher than World Health Organization standards. CSICU nurses are exposed to noise levels that can affect their hearing capacity. Further research isneeded for effective medical device–alarm management.Keywords: ambient noise, intensive-care unit, nurses, audiometry, hospital